Entropy production and heat transport in harmonic chains under time-dependent periodic drivings - Akasaki, Bruno Augusto Naves (2020)
We study the properties of interacting linear chains subject to periodic drivings through the framework of stochastic thermodynamics. The systems are described by Fokker-Planck-Kramers equation and exact solutions are obtained as functions of the modulation frequency and strength constants. Analysis will be carried out for short and long chains. In the former case, explicit expressions are derived for a chain of two particles, in which the entropy production is written down as a bilinear function of thermodynamic forces and fluxes, whose associated Onsager coefficients are evaluated for distinct kinds of periodic drivings. The limit of long chains is analyzed by means of a protocol in which the intermediate temperatures are self consistently chosen and the entropy production is decomposed as a sum of two individual contributions, one coming from real baths (placed at extremities of lattice) and other from self-consistent baths. Whenever the former dominates for short chains, the latter contribution prevails for long ones. It was also possible to verify that the thermal reservoirs leads to a heat flux according to Fouriers law as well as the behavior of the entropy production with a inclusion of a lag and the behavior of the optimal frequency in relation to the problem parameters.